KEDUDUKAN PERATURAN NAGARI DALAM PERSPEKTIF HUKUM TATA NEGARA (Studi Pembentukan Peraturan Nagari di Manggilang) - Maizi Fahdela Agustin (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2022)
A written regulation is needed in a Nagari to guide the leader of Nagari that is called by Wali Nagari to run his government. However, these days, in Nagari the regulation used is the unwritten regulation that only shared among the community. This study aims to encourage to form the Nagari Regulation especially for Nagari Manggilang. This study was carried out in a normative-empirical manner by conducting interviews and observations. The data found will be strengthened by various government regulations to obtain a more scientific study. From the findings during the research, the authors found that the Nagari Regulations are still recognized and have binding legal force even though they are not stated in detail on the types of hierarchy of laws and regulations in Indonesia. Meanwhile, the process of forming Nagari Regulations in Nagari Manggilang includes the pre-implementation, implementation, and post implementation. In the pre-implementation stage, it was found that the authority of the KAN institution was not fully fulfilled so that it was not in accordance with the mandate of the Regional Regulation of West Sumatra Province Number 7 of 2018 concerning Nagari. Therefore, there should be special regulations related to the institutions authorized to form Nagari regulations in Nagari Manggilang.